Improving substance misuse outcomes in contingency management treatment with adjunctive formal psychotherapy: a systematic review and meta-analysis - Thomas Steare; Sonia Johnson; Luke Sheridan Rains; Oliver Mason (BMJ Open)
Objectives Contingency management (CM) is a treatment for substance misuse that involves the provision of incentives. This review examines the hypothesis that adding another formal psychotherapy, such as cognitive–behavioural therapy (CBT) or motivational enhancement therapy (MET), to CM improves substance use outcomes at both treatment end and at post-treatment follow-up compared with CM only.Data sources Searches were performed in December 2017 and July 2019 of seven electronic bibliographic databases (MEDLINE, PsycINFO, EMBASE, Scopus, Web of Science, CINAHL, PsycEXTRA), as well as online trial registries and EThoS, and were followed by reference list screening.Eligibility criteria Included studies were randomised controlled trials of adults (18–65) who were using illicit substances, alcohol or tobacco. Studies featured an experimental arm delivering CM combined with a structured evidence-based psychotherapeutic intervention and a CM-only arm. Studies published up to July 2019 were included.Data extraction and synthesis The primary outcome was biometrically verified point prevalent abstinence (PPA) at treatment end. Secondary outcomes included biometrically verified PPA at post-treatment follow-up and self-reported days of use at treatment end and post-treatment follow-up. Pooled risk ratios for PPA outcomes and standardised mean differences for days of use were calculated using random effects models. Risk of bias was assessed using the Grading of Recommendations Assessment, Development and Evaluation.Results 12 studies (n=1654) were included. The primary analysis found no evidence of a synergistic effect in PPA at treatment end (relative risk (RR) 0.97, 95% CI 0.85 to 1.09; p=0.57). Sensitivity analysis of studies featuring CBT/MET also found no evidence of an effect (RR 0.92; 95% CI 0.79 to 1.08; p=0.32). None of the secondary outcomes showed any evidence of benefit.Conclusion The results of the meta-analyses found no evidence that combining CM with another intervention improves the short-term or long-term effects of CM treatment.